Analysis of morphological changes after facial massage by a novel approach using three‐dimensional computed tomography. Issue 3 (22nd November 2016) - Nishimura, H.; Okuda, I.; Kunizawa, N.; Inoue, T.; Nakajima, Y.; Amano, S.
Abstract : Background/purpose: Photograph‐based visual scoring has been used for evaluation of facial morphological changes. Here, we describe a three‐dimensional computed tomography (3D‐CT) method for objective analysis of facial and intra‐facial (subcutaneous) changes. The effects of facial massage were examined using both methods. Methods: Subjects were 12 healthy female volunteers without facial scars or deformation (age 30–54 years, mean 39.4 years). Photograph‐based scoring of massage‐induced morphological changes was done at the nasolabial folds, upper, lower and lateral cheeks and lower eyelids. For 3D‐CT evaluation, the virtual center axis (VCA) was set as the cranio‐caudal longitudinal line, and the VCA‐skin surface distances (VSDs) were measured. Massage‐induced changes of VSD were calculated (facial massage‐induced change rate, FMCR). Intra‐facial (subcutaneous) changes were also evaluated. Results: Photograph‐based scoring revealed marked morphological changes of the nasolabial folds after facial massage, and changes of the lower, upper and lateral cheeks and lower eyelid were also observed in more than half of the subjects. FMCR values were significantly changed in the paranasal area, nasolabial fold area and cranial part of the mandibular area. Photograph‐based scores at the lower cheek and lower eyelid were well correlated with FMCR in the inferior part of the nasolabial fold and the mandibular area, respectively. Massage‐induced changes of subcutaneous fat tissues and facial expression muscles were also apparent on CT images. Conclusion: 3D‐CT imaging is useful for objective evaluation of the effects of facial massage, including anatomical changes in subcutaneous structures.